1993
DOI: 10.1083/jcb.121.3.665
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ras p21 in neurotrophin-induced response of sensory, but not sympathetic neurons.

Abstract: Abstract. Little is known about the signal transduction mechanisms involved in the response to neurotrophins and other neurotrophic factors in neurons, beyond the activation of the tyrosine kinase activity of the neurotrophin receptors belonging to the trk family. We have previously shown that the introduction of the oncogene product ras p21 into the cytoplasm of chick embryonic neurons can reproduce the survival and neurite-outgrowth promoting effects of the neurotrophins nerve growth factor (NGF) and brain-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…Ras activation supports the survival of some neurons following TFD [Borasio et al, 1993;Nobes and Tolkovsky, 1995]. Conversely, inhibition of the Ras/MEK/ ERK pathway by PD98059 does not induce sympathetic neuron cell death [Virdee and Tolkovsky, 1996], consistent with alternative survival pathways in neurons.…”
Section: Mek/erk Signaling Pathwaymentioning
confidence: 67%
“…Ras activation supports the survival of some neurons following TFD [Borasio et al, 1993;Nobes and Tolkovsky, 1995]. Conversely, inhibition of the Ras/MEK/ ERK pathway by PD98059 does not induce sympathetic neuron cell death [Virdee and Tolkovsky, 1996], consistent with alternative survival pathways in neurons.…”
Section: Mek/erk Signaling Pathwaymentioning
confidence: 67%
“…ras activity is likely to be important in axon growth (Borasio et al, 1993;Boguski and McCormick, 1993 ) . Syp protein is concentrated in growth cones in E7 forebrain (J. Perron and J.L.B., unpub.…”
Section: H P T Q S K Q a Q D Y G D I T V A M T S E I~p E W T I R D F mentioning
confidence: 98%
“…Several studies have suggested that Ras and its downstream effectors Raf-MEK-MAPK are critical mediators of GF-induced survival in a number of different cell types (Borasio et al 1989(Borasio et al , 1993Nobes and Tolkovsky 1995). It is now clear that the Raf-MEK-MAPK cascade does under some circumstances promote cell survival (Xia et al 1995;Parrizas et al 1997;Bergmann et al 1998;Kurada and White 1998;Meier and Evan 1998;Anderson and Tolkovsky 1999;Bonni et al 1999;Shimamura et al 1999).…”
Section: Pi3k and Cell Survivalmentioning
confidence: 99%